2010
DOI: 10.2337/dc10-0819
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Glucose Tolerance in Pregnancy Affects Fetal Insulin Sensitivity

Abstract: OBJECTIVEOffspring of mothers with impaired glucose tolerance are far more likely to develop type 2 diabetes. We tested the hypothesis that maternal glucose tolerance in pregnancy affects fetal insulin sensitivity or β-cell function.RESEARCH DESIGN AND METHODSIn a prospective singleton pregnancy cohort study, we analyzed glucose, insulin, and proinsulin concentrations in maternal blood at the 50-g oral glucose tolerance test (OGTT) at 24–28 weeks of gestation and in venous cord blood (n = 248). The cord blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 23 publications
8
79
0
1
Order By: Relevance
“…Cord plasma DHA (but not AA) levels were significantly lower in the newborns of gestational diabetic pregnancies than non-diabetic pregnancies (∼ 17.1% lower in relative weight, P  = 0.01) ( Table 2 ), despite similar cord blood glucose concentrations (4.6 vs. 4.8 mmol/L, P  = 0.47) indicating adequate management of diabetes in the study cohort [17]. A similar pattern was observed for eicosapentaenoic acid (EPA; C20∶5n-3; ∼33.3% lower in gestational diabetic pregnancies, P  = 0.02).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Cord plasma DHA (but not AA) levels were significantly lower in the newborns of gestational diabetic pregnancies than non-diabetic pregnancies (∼ 17.1% lower in relative weight, P  = 0.01) ( Table 2 ), despite similar cord blood glucose concentrations (4.6 vs. 4.8 mmol/L, P  = 0.47) indicating adequate management of diabetes in the study cohort [17]. A similar pattern was observed for eicosapentaenoic acid (EPA; C20∶5n-3; ∼33.3% lower in gestational diabetic pregnancies, P  = 0.02).…”
Section: Resultsmentioning
confidence: 92%
“…In a prospective singleton pregnancy cohort study in Montreal, Canada, we have shown that gestational diabetes may impair fetal insulin sensitivity [17]. To further study the potential impact of fatty acids on fetal insulin sensitivity, maternal and cord plasma specimens were used to measure fatty acids in a subset of the cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin is the primary driver of fetal IGF-I production (2). The higher fetal IGF-I levels in gestational diabetes could be attributable to elevated fetal insulin secretion (15,16). We speculated that the higher maternal IGF-I levels in gestational diabetes could be due to enhanced secretion of placental GH, the main driver of maternal IGF-I production in pregnancy (9).…”
Section: Comparisons With Previous Findingsmentioning
confidence: 97%
“…Maternal and cord blood specimens from a recent prospective pregnancy cohort study (15) were used to investigate maternal and fetal IGF-I and IGF-II levels and their associations with fetal growth. The study was approved by the research ethics committees of participating hospitals.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation